Cystatin from the helminth Ascaris lumbricoides upregulates mevalonate and cholesterol biosynthesis pathways and immunomodulatory genes in human monocyte-derived dendritic cells - Acevedo, Nathalie; Lozano, Ana; Zakzuk, Josefina; Llinás-Caballero, Kevin; Brodin, David; Nejsum, Peter; Williams, Andrew R.; Caraballo, Luis (Frontiers in Immunology, 2024)
Background: Ascaris lumbricoides cystatin (Al-CPI) prevents development of allergic airway inflammation and dextran induced colitis in mice models. It has been suggested that helminth derived cystatins inhibit cathepsins in dendritic cells (DC), but their immunomodulatory mechanisms are unclear. We aimed to analyze the transcriptional profile of human monocyte derived DC (moDC) upon stimulation with Al-CPI to elucidate target genes and pathways of parasite immunomodulation. Methods: moDC were generated from peripheral blood monocytes from six healthy human donors of Denmark, stimulated with 1 µM of Al-CPI and cultured for 5 hours at 37°C. RNA was sequenced using TrueSeq RNA libraries and the NextSeq 550 v2.5 (75 cycles) sequencing kit (Illumina, Inc). After QC, reads were aligned to the human GRCh38 genome using STAR. Differential expression was calculated by DESEq2 and expressed in fold changes (FC). Cell surface markers and cytokine production by moDC were evaluated by flow cytometry. Results: Compared to unstimulated cells, Al-CPI stimulated moDC showed differential expression of 444 transcripts (|FC| ≥1.3). The top significant differences were in kruppel like factor 10 (KLF10, FC 3.3, PBH = 3 x 10-136 ), palladin (FC 2, PBH = 3 x 10-41 ) and the low-density lipoprotein receptor (LDLR, FC 2.6, PBH = 5 x 10-41 ). Upregulated genes were enriched in regulation of cholesterol biosynthesis by sterol regulatory element-binding proteins (SREBP) signaling pathways and immune pathways. Several genes in the cholesterol biosynthetic pathway showed significantly increased expression upon Al-CPI stimulation, even in the presence of LPS. Regarding the pathway of negative regulation of immune response, we found significant decrease in cell surface expression of CD86, HLA-DR and PD-L1 upon stimulation with 1 µM Al-CPI. Conclusion: Al-CPI modifies the transcriptome of moDC, increasing several transcripts encoding enzymes involved in cholesterol biosynthesis and SREBP signaling. Moreover, Al-CPI target several transcripts in the TNF-alpha-signaling-pathway influencing cytokine release by moDC. In addition, mRNA levels of genes encoding KLF10 and other members of the TGF beta and the IL-10 families were also modified by Al-CPI stimulation. The regulation of the mevalonate pathway and cholesterol biosynthesis suggests new mechanisms involved in DC responses to helminth immunomodulatory molecules.